Review of forensic medicine and toxicology includes MCQS & answers from PG entrance examination - Biswas, Gautam (Jaypee Brothers, 2010)
A comprehensive, clear and concise book covering the whole syllabus as prescribed by Medical Council of India Provides up-to-date information on forensic issues in day to-day practice. Assembles an impressive array of topics and substantial amount of material in a nutshell. Some topics are in detail like Medical Jurisprudence, Identification, Autopsy, Injuries, Sexual Offences, Forensic Psychiatry and Toxicology depending upon the weightage given in entrance examination. The contents of each chapter are crisp and to the point along with required flow charts. The uniqueness of the book lies with the tables, differentiations, flow charts and line diagrams which make it easier to the students to grasp the subject wel.l A valuable masterpiece in the subject reflecting the eminence and competence of the author. Spread over 63 chapters, the book has been written in a lucid style, using simple language, MCQs and earmarking questions of importance.